Meeting decision support requirements through natural capital accounts: a case study in England's National Nature Reserves. Issue 1 (2nd January 2023) - Sunderland, Tim; Marsh, Dan; Lusardi, Jane; Hudson, Cat; Waters, Ruth
ABSTRACT: Natural Capital Accounts extend traditional balance sheets to include valuation of non-market environmental benefits and asset values. They aim to bring the often-overlooked value of nature into decision-making, thus providing an effective decision-support tool. We compare Natural Capital Accounts to UK decision-support guidance, which leads us to three innovations that we apply to a case study of the National Nature Reserves in England. First, we use a reporting format, which explicitly reports gaps in quantification and valuation. Second, we provide 'traffic-light', confidence level information for our value results. Third, we report on the ecological state of assets and incorporate this evidence into the headline results. These innovations address common weaknesses whereby partial monetary values may mislead decision-makers and confidence levels are highly variable, yet often ignored. Information on the ecological state of assets is often only partial, non-systematic and not presented with the summary results. Producing this account required ecological and economic evidence to be treated as equally important. These three innovations produce an account that is transparent and provides a useful snapshot of the condition of natural capital assets.